Score-Driven Systemic Risk Signaling for European Sovereign Bond Yields and CDS Spreads - Rutger-Jan Lange; Andre Lucas; Arjen H. Siegmann (Tinbergen Institute, 2016)
We compute joint sovereign default probabilities as coincident systemic risk indicators. Instead of commonly used CDS spreads, we use government bond yield data which provide a longer data history. We show that for the more recent sample period 2008–2015, joint default probabilities based on CDS and bond yield data yield similar results. For the period 1987-2008, only the bond yield data can be used to shed light on European sovereign systemic stress. We also show that simple averages of rolling pairwise correlations do not always yield intuitive systemic risk indicators.
Keywords: G01; G17; C32; 330; systemic risk; conditional default; credit default swaps; bond yields